Enhanced performance of UV photodetector of MoS2 quantum dots-decorated ZnO nanorods. Issue 6 (March 2021) - Putri, N A; Fauzia, V; Isnaeni, I; Lewa, I; Imawan, C
Abstract: Two-dimensional transition metal dichalcogenides such as molybdenum disulfide (MoS2 ) have attracted great attention due to their unique optical, electrical and chemical properties. MoS2 quantum dots (QDs) exhibit strong quantum confinement, high surface area and notable active edge sites compared to their bulk. In this work, MoS2 QDs were attached on the surface of ZnO nanorods (NRs) grown on interdigitated ITO substrates and then used as photodetector. MoS2 QDs were synthesized by a new ultrafast way pulsed laser ablation (PLA) in liquid method and then spincoated on the surface of ZnO NRs. The pristine ZnO and ZnO/MoS2 QDs photodetector were investigated under UV and visible light (325 nm, 505 nm and 635 nm) with the bias voltage -5 V to 5 V. The results show that the decoration of ZnO NRs by MoS2 QDs could enhance the sensitivity, responsivity and detectivity under UV irradiation. This may due to the decrease of dark current as the result of passivation of surface defects of ZnO NRs by MoS2 QDs.